2015
DOI: 10.3201/eid2108.150652
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Emerging Norovirus GII.17, United States, 2014

Abstract: To determine whether the norovirus strain GII.17 recently detected in Maryland, USA, (Hu/GII.17/Gaithersburg/2014/US) is spreading globally, we characterized the genome. High similarity with the norovirus GII.17 that caused recent outbreaks in Asia indicates that the same strain was present in the United States during the 2014–15 norovirus season (winter).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 11 publications
3
93
0
Order By: Relevance
“…According to global trends, it was expected that HuNoV GII.17 would be detected more consistently than GII.4 in Korea. While HuNoV GII.17 was detected during 2013−2014, similar to the results for China, the US and Europe, HuNoV GII.4 was detected in 2015 [13][14][15][16][17], and was also detected along with HuNoV GII.17 in 2016 (Table 2 and Fig. 2).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…According to global trends, it was expected that HuNoV GII.17 would be detected more consistently than GII.4 in Korea. While HuNoV GII.17 was detected during 2013−2014, similar to the results for China, the US and Europe, HuNoV GII.4 was detected in 2015 [13][14][15][16][17], and was also detected along with HuNoV GII.17 in 2016 (Table 2 and Fig. 2).…”
supporting
confidence: 59%
“…One sample contained both GI.3 and GI.7, and both were included in the overall count (Table 2) HuNoV GI and GII genotypes (GII. 2,5,7,9,11,12,14,15,16,18,19,20, and 21) were not found ( Table 2). …”
mentioning
confidence: 93%
“…Genotyping of the sym- (winter) [37] and it remains to be seen if the currently dominant NoV strain GII.4 Sydney 2012 will be replaced in other parts of the world [38] . It is crucial for the vaccine development and evaluation, because A virus [39] .…”
Section: Gii4 Syndey As the Course Of Outbreaks Inmentioning
confidence: 99%
“…However, starting in November 2014, a novel NoV genotype GII.17 was reported to cause diarrheal disease outbreaks, worldwidely [2, 5, 1416] and Matesushiam et al [5] found that this novel genotype had a polymerase sequence and amino acid substitutions in the capsid region. In this study, we reported that the GII.17 genotype was first detected in diarrheal patients in August 2014, which was earlier than the first reported outbreak in Jiangsu [3].…”
mentioning
confidence: 99%